A Quantum Theory of Gravity Based on Physical Time - Ittipat Roopkom; Pichet Wisartpong; Wirote Jongchanachavawat; Stout, Beverly F.; Thawatchai Mayteevarunyoo; Paramote Wardkein (Zenodo (CERN European Organization for Nuclear Research), 2026)
For over a century, the "Problem of Time" has locked General Relativity and Quantum Mechanics in irreconcilable opposition—one treats time as geometry, the other as an external parameter. This paper breaks the deadlock with a radical but minimal proposal: make time physical. We elevate the measurable rate of clocks, γ=dt/dτ, to a dynamical scalar field ψ=lnγ. From a single, self-contained action, we derive one unifying master equation that governs the response of time itself. No quantization postulate is added. No spacetime geometry is quantized. From this single field equation, both pillars of modern physics emerge as distinct regimes of the same underlying reality: Gravity (Macroscopic): The spatial gradient of ψ recovers the Newtonian potential exactly. Mass moves toward slower time—this is gravity. Quantum Mechanics (Microscopic): In vacuum, fluctuations δψ obey the exact Klein–Gordon equation. Quantum behavior is mathematically shown to be wave-like excitations of time itself. Nature does not need two contradictory rulebooks. Classical gravity and quantum mechanics are not separate theories to be reconciled. They are scale-dependent manifestations of a single physical entity: the dynamical response of time. No extra dimensions. No independent postulates. Just time, made real.
Keywords: Relativity and Gravitational Theory; Quantum Mechanics and Applications; Noncommutative and Quantum Gravity Theories